Association between preventive behaviour and anxiety at the start of the COVID-19 pandemic in Slovenia - Velikonja Nevenka Kregar; Erjavec Karmen; Verdenik Ivan; Hussein Mohsen; Velikonja Vislava Globevnik (Sciendo, 2020)
The first large outbreak of SARS-CoV-2 in Europe occurred in Northern Italy in February 2020. The relatively fast spread of the infection to Slovenia was expected, and preventive measures for its suppression were widely discussed.